90-day oral toxicity study of a salmon nasal cartilage extract containing undenatured collagen and proteoglycan in Sprague-Dawley rats - Kenji Takada; Hideharu Nakano (PLoS ONE, 2026)
Salmon nasal cartilage is a rich source of proteoglycan and collagen that is widely used in food products. In Japan, a novel extraction method has been developed and patented that enable the simultaneous production of proteoglycan and undenatured collagen from salmon nasal cartilage. This study evaluated the subchronic oral toxicity of this extract mixture (SCP Complex-LS, containing 40% proteoglycan and 40% undenatured collagen) in a 90-day repeated toxicity study in Sprague-Dawley rats, following by a 14-day recovery period. Rats (20/group; 10 males and 10 females) were administered SCP Complex-LS once daily by oral gavage at doses of 0 (vehicle), 10.3, 20.6, or 41.2 mg/kg body weight/day, with additional recovery groups (10/groups; 5 males and 5 females) receiving vehicle or the high dose. Clinical endpoints included mortality, clinical observations, body weight, food consumption, estrous cyclicity, ophthalmoscopy, clinical pathology, organ weights, gross pathology, and histopathology. No deaths or test item-related clinical signs were observed. Sporadic changes in hematological, biochemical, urinary, or organ weight parameters occurred in some dose groups but were small in magnitude, showed no consistent dose-response relationship, and were not corroborated by histopathological alterations. Histopathology revealed only minimal findings, such as mild inflammation or congestion in the liver, kidneys, and lungs, occurring at low incidence and with similar frequency in both control and high-dose groups. Estrous cycles remained within normal limits, and recovery groups showed no evidence of delayed or irreversible toxicity. Based on these findings, the No Observed Adverse Effect Level (NOAEL) for SCP Complex-LS was determined to be 41.2 mg/kg body weight/day in Sprague-Dawley rats under the conditions of this study, supporting its safety for use as a food ingredient within the expected range of human intake.